Towards a more social and cooperative behaviour in physical education: sport education model application - Sierra-Díaz, M. J.; Evangelio, C.; Pérez-Torralba, A.; González-Víllora, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The purpose of this investigation is to evaluate and to compare the Sport Education Model (SEM) implementation together with the presence or the absence of pedagogical strategies, which encourage prosocial behaviour among the participants. The sample consisted of two Primary sixth level classes (n = 51; 10.72 ± .66). Among group A, methodologies oriented to foster the prosocial behaviour were developed. Among group B, strategies centred in the individual improvements were developed. Though a one-way ANOVA, pre-test and post-test results of the Antisocial Behaviour Questionnaire (Martorell y González, 1992) were analysed. Results shows significant differences among scores in both classes before starting the model and after it (p = .000). It is observed a significant reduction of antisocial performances among the total scores of the post-test in group A (p = .000). Model-based implementation in Physical Education, Sport Education between them, should be complemented with methodological strategies that encourage prosocial behaviours because it favors positively the students’ values education.